The Main Character's Neurotic Anxiety in The Novel Terminal Cinta Terbaru by Ashadi Siregar Analysis: Psychological Literature - Manulang, Sudarso (L'Geneus : The Journal Language Generations of Intellectual Society, 2019)
The novel as a result of the author's thoughts contains a series of stories about the life of the characters. This characterization is clearly illustrated by how the psychological shape of the character is. The main character in the novel Terminal Cinta Terbaru by Ashadi Siregar experiences a form of mental disorder. The form of psychiatric disorder experienced is neurotic anxiety. Neurotic anxiety is a feeling of anxiety that arises in oneself unconsciously because of a character's instinct to consider all the actions performed by the character. The analysis of research on the behavior of characters who see in terms of psychology that occurs in characters in literature is psychosastra.